Rapid Single Cell Detection of Lactic Acid Bacteria in the Beer Using Bioluminescence Method - TAKAHASHI, TOSHIHIRO; NAKAKITA, YASUKAZU; NAKAMURA, TAKESHI (Biocontrol Science, 2019)
In this study, we developed a system, known as MicroStarTM Rapid Microbe Detection System (RMDS) , to detect Lactobacillus brevis, which usually requires 2-4 days for examination by the conventional plate count procedure, for beer quality control using a bioluminescence method within 24 hr and also aimed to develop a technology to detect bacterial growth without the need for cultivation. We used a highly sensitive luminous reagent that increased the activity of the luciferin- luciferase reaction to 2.5×10－18 mol ATP/0.2 μl and could detect even a single lactic acid bacterial cell. The limitation of the method was that ATP derived from the beer hindered bacterial measurement and the supply of energy source to secure ATP of lactic acid bacterial cell. The sample beer was filtered through a membrane filter, avoiding the formation of beer foam to the best extent, the filter was cleaned with 10% ethanol and 0.1% sodium hydrogen carbonate solution, and incubated on a GMY agar plate (1% glucose, 0.2% malic acid, 0.67% yeast nitrogen base, 1% agar; pH 5.2) at room temperature for 2 hr. Post incubation of the filter, bacterial cell count was measured with RMDS. This method could overcome the hindrance of ATP measurement and could stably detect lactic acid bacteria without the need for cultivation.